[OP.3C.08] ELEVATED PULSE PRESSURE IN YOUNG TO MIDDLE AGE MEN CARRIES A REDUCED RISK OF ADVERSE OUTCOME. (September 2017) - Saladini, F.; Fania, C.; Mos, L.; Mazzer, A.; Garavelli, G.; Bortolazzi, A.; Casiglia, E.; Palatini, P.
Abstract : Objective: Elevated pulse pressure (PP) is a well recognized predictor of adverse outcome in elderly hypertensive subjects whereas its clinical significance in young individuals remains controversial. The aim of the present study was to investigate the clinical significance of elevated PP in young-to-middle-age subjects screened for stage 1 hypertension. Design and method: We examined 1241 18-to-45-year-old participants from the HARVEST study. The predictive role of PP versus mean blood pressure (MBP) for incident hypertension and cardiovascular events (CVE) was evaluated in Cox survival analyses, adjusting for risk factors and several confounders. Results: PP was inversely related to age in men (r = −0.29, p < 0.001) and directly related to age in women (r = 0.18, p = 0.002). In multivariate regression analysis including BMI and lifestyle factors, significant determinants of PP were male gender (p < 0.001), younger age, (p < 0.001), physical activity (p < 0.001), heart rate (p < 0.001), and stroke volume (N = 829, p < 0.001). During 12.1 years of follow-up (IQR = 5.1–17.4), 65.0% of participants developed hypertension requiring pharmacological treatment. In Cox models adjusted for age, sex, BMI, heart rate and lifestyle factors, participants in the highest PP tertile had a reduced risk of incident hypertension compared to those of the bottom tertile (HR, 0.70; 95%CI, 0.58–0.85, p < 0.001). In contrast, participants in the top MBP tertile had an increase in risk (1.33, 1.10–1.62, p = 0.0039). In sensitivity analyses, these associations held true in men (HR, 0.65; 95%CI, 0.52–0.81, p < 0.001 for PP, and 1.50, 1.20–1.89, p < 0.001, for MBP) but not in women (p > 0.49 for PP and MBP). CVE were developed by 6.0% of participants. In multivariable Cox models, participants in the highest PP tertile had a reduced risk of CVE (HR 0.46; 95%CI, 0.24–0.89, p = 0.021) and those in the top MBP tertile had a marked increase in risk (3.43, 1.60–7.35, p = 0.0016). Again, these associations remained significant among the men (0.47, 0.23–0.96, p = 0.040, for PP, and 3.89, 1.56–9.72, p = 0.0038, for MBP), but not among the women (p > 0.30 for PP and MBP). Conclusions: These data show that in men younger than 45 years, only MBP is a predictor of hypertension needing treatment and of CVE whereas high PP even carries a reduced risk of adverse outcome.